Treating juvenile idiopathic arthritis to target: what is the optimal target definition to reach all goals? - Schoemaker, Casper G. (Pediatr Rheumatol Online J, 2020)
In 2018, an international Task Force formulated recommendations for treating Juvenile Idiopathic Arthritis (JIA) to target. The Task Force has not yet resolved three issues. The first issue is the lack of a single “best” target. The Task Force decided not to recommend the use of a specific instrument to assess inactive disease or remission. Recent studies underscore the use of a broad target definition. The second issue is the basic assumption that a treatment aggressively aimed at the target will have ‘domino effects’ on other treatment goals as well. Thus far, this assumption was not confirmed for pain, fatigue and stiffness. The third issue is shared decision-making, and the role of individual patient targets. Nowadays, patients and parents should have a more active role in choosing targets and their personal treatment goals. In our department the electronic medical records have been restructured in such a way that the patient’s personal treatment goals with a target date appears on the front page. The visualization of their specific personal goals helps us to have meaningful discussions on the individualized treatment strategy and to share decisions. In conclusion, a joint treat to target (T2T) strategy is a promising approach for JIA. The Task Force formulated valuable overarching principles and a first version of recommendations. However, implementation of T2T needs to capture more than just inactive disease. Patients and parents should have an active role in choosing personal targets as well.